Effect of Pre-Deformation on the Microstructure and Precipitation Behavior of Spray-Formed 7xxx Series Aluminum Alloys - Huiying Hou; Lei Zhang; Shuohao Xing; Hongchao Zhai; Shule Xia; Long Zhai; Zhijie Wang; Sha Liu (Metals)
This study investigates the effect of pre-deformation on the microstructure and precipitation behavior of spray-formed 7xxx series aluminum alloys. Pre-deformation introduces a high density of dislocations, increasing the proportion of low-angle grain boundaries from 40% to 66%. After solution treatment at 580 °C, grain size significantly increases, ranging from 35 µm to 315 µm, with a higher proportion of larger grains observed in pre-deformed samples. Subsequent aging treatment refines the microstructure, resulting in grain sizes between 30 µm and 270 µm, and leads to a more uniform precipitate distribution.